The effect of e-service quality on purchase decisions with E-WOM as a moderating variable on 4-star hotels in West Sumatra - Surenda, Rian; Adrian, Arif; Abrian, Youmil; Fansurya, Alfi Husni (Jurnal Pendidikan Teknologi Kejuruan, 2022)
This research is based on changes in consumer behavior in deciding to purchase hotel room services in West Sumatra, post-covid-19 consumer behavior has an impact on hoteliers in determining marketing strategies, this study aims to see the relationship between variables, namely E-Service Quality on purchasing decisions and see the effect of the E-wom variable as a moderator on purchasing decisions. This research was conducted in West Sumatra with a sample of 120 hotel guests, using a purposive sampling technique, where the sample was determined by the criteria of having stayed at a hotel and making hotel room reservations online. This study uses the help of PLS techniques to determine the inner and outer variables, where the variables measured are E-Service quality, Purchase Decision, E-WOM as a moderating variable. The results show that E-Service Quality has a significant positive effect on purchasing decisions and E-WOM moderates E-Service quality significantly positive on purchasing decisions.